The Effectiveness of the ASSURE Learning Model Assisted by Google Classroom in Improving Students' Mathematical Literacy in Transformational Materials - Reza Oktiana Akbar; Zaituni Zaituni (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
In theory, the Google Classroom-assisted ASSURE learning model can improve students' mathematical literacy in learning mathematics because the Google Classroom-assisted ASSURE learning model can be adapted to the material to be delivered to students, student conditions, available resources and competencies that students can master. The purpose of this study was to determine the effectiveness of the google classroom-assisted ASSURE learning model in increasing students' mathematical literacy. This study used a quantitative method using a Pretest-Posttest Control Group Design with a population of class IX students at SMPN 1 Gempol. The sample of this research was class IX D as the experimental class and class IX B as the control class which were selected through cluster random sampling technique. Learning process data were obtained using implementation observation sheets while students' mathematical literacy data were obtained through students' mathematical literacy tests and questionnaires. The results of data analysis show that the ASSURE learning model assisted by Google Classroom is effective in increasing students' mathematical literacy.